Nutraceutical potential of Pennisetum typhoides microgreens: In vitro evaluation of antioxidant and antibacterial activities and in silico Staphylococcus aureus FtsZ inhibition. (August 2021) - Sharma, Ratnika; Gupta, Promila
Abstract: The objective of this study was to evaluate and identify the components of microgreens harvested from Pennisetum typhoides (Pearl millet) for their antioxidant and antimicrobial activities besides finding the possible mechanism of inhibition of Staphylococcus aureus filamentous temperature-sensitive protein Z (FtsZ) in-silico . Initially, methanolic extracts of microgreens from five to ten days post germination (dpg) stages of two pearl millet varieties (PC-383 and PC-612) were compared for total phenolics content (TPC), total flavonoids content (TFC) and antioxidant activity using in vitro assays: DPPH and ABTS + radical scavenging. Eighth dpg showed the highest antioxidant activity and best correlation with the amount of phytochemicals. Further, its sequential extracts with solvents of increasing polarities were compared for antioxidant potential. Antibacterial activity was tested using Kirby-Bauer disc diffusion method and minimum inhibitory concentration (MIC) was determined using broth macrodilution method. Aqueous extracts (AE) had highest antioxidant activity and lowest MIC against S. aureus (0.125 mg/ml). Phenolic acids composition of AE was determined by ultra-fast liquid chromatography (UFLC) followed by docking with S. aureus FtsZ protein. Chlorogenic acid (CHA) was found to have lowest binding energy (ΔG -9.21 kcal/mol) and lowest inhibition constant (Ki 176.05 nM). In comparison with a known inhibitor of S. aureus FtsZ (PC-190723), molecular dynamics simulation studies depicted its stable interaction as assessed via root mean square deviation (RMSD), root mean square fluctuation (RMSF) and the number of hydrogen bonds were found comparable. This novel finding points toward further exploring and utilizing these microgreens for bioactives with nutraceutical potential. Highlights: Eighth day post germination (dpg) microgreen extracts show maximum antioxidant content. Eighth dpg aqueous extracts have maximum polyphenols, antioxidant and antimicrobial activities. UFLC confirmed the presence of six phenolic acids. Molecular docking and dynamics show chlorogenic acid interacts with FtsZ.